To Touch or Not to Touch? An Ethical Reflection and Case Study on Physical Touching in the Pastoral Accompaniment of Vulnerable Persons, Especially Minors and Persons with Intellectual Disabilities - Axel Liégeois (Religions, 2023)
Our aim is to develop an ethical reflection and a case study on physical touching by Christian chaplains in their pastoral accompaniment of minors and persons with intellectual disabilities. To this end, we develop an ethical evaluation method consisting of four elements: context; motives; possible actions; and effects. Following this method, we highlight how to evaluate physical touch, formulate ten ethical recommendations, and discuss a case study. Regarding the context of the asymmetric relationship, our recommendations are for chaplains to (1) deal with power in a responsible way and (2) foster their sense of responsibility. Given the complexity of chaplains’ motives, we recommend that chaplains (3) clarify their motives and (4) strengthen their integrity. For the ambiguity of physical touch, we recommend chaplains to (5) seek the appropriateness of touch, (6) consider age and development, and (7) nurture professional ethics. As for the multiplicity of effects for vulnerable persons, our recommendations for chaplains are to (8) give priority to the vulnerable person, (9) not cause harm, and (10) obtain free and informed consent. We encourage chaplains to touch vulnerable persons when appropriate for pastoral accompaniment but to be particularly careful about the use of power and to make a strong effort to obtain consent for touching.